PROFILE OF MEDICAL STUDENTS' METACOGNITIVE SELF-REGULATED LEARNING STRATEGIES IN PBL GROUP DISCUSSION DURING THE LIMITED FACE-TO-FACE LEARNING PERIOD - Widiartini, Catharina; Ferine, Miko (Universitas Gadjah Mada, 2023)
Background: The change in the learning environment, from fully online to limited face-to-face could affect the use of metacognitive self-regulated learning (SRL) strategies in carrying out Problem-Based Learning (PBL) group discussions as one of the main learning methods in the faculty of medicine in Indonesia or elsewhere. The study aimed to describe the profile of metacognitive SRL strategies in conducting PBL group discussions during the limited face-to-face learning period.Methods: This was a descriptive quantitative observational study conducted at The Faculty of Medicine, Universitas Jenderal Soedirman during the implementation of limited face-to-face learning in the even semester of 2021/2022. Undergraduate students selected by total sampling were asked to fill in a questionnaire that was adapted from the MSLQ. The frequency of a learning strategy application for each of the 22 examples of metacognitive SRL strategies differed into: never; rarely; frequently; or always.Results: The response rate was 57.93% (199 students). Most (70.4%) of the respondents were women and had an average of 19.6 years old. Learning strategies with the largest proportion of